Reducing Passenger Complaints through Targeted Inflight Coaching: A Quantitative Assessment - Maida Nkonye Asata; Daphine Nyangoma; Chinelo Harriet Okolo (International Journal of Scientific Research in Civil Engineering, 2023)
In the airline sector, passenger complaints continue to be a persistent problem that frequently affects operational effectiveness, customer loyalty, and brand perception. There is little empirical data on the efficacy of focused in-flight coaching in resolving real-time service delivery challenges, despite the fact that many airlines have put in place extensive service training programs. This uses a quantitative evaluation of crew performance and feedback metrics to investigate how targeted in-flight coaching affects the decrease in passenger complaints. This study uses a quasi-experimental approach to compare complaint frequencies and categories across flights with and without onboard coaching interventions using data gathered from three international airlines over a 12-month period. Experienced trainers implanted on specific aircraft provided in-flight instruction, which included post-flight feedback sessions and real-time support. Post-flight surveys and customer relations databases were used to track passenger complaints, which were grouped into service delivery domains like communication, responsiveness, courtesy, and problem resolution. Targeted coaching interventions significantly decreased total flight complaint rates, according to statistical analysis utilizing regression modeling and paired t-tests. Remarkably, passenger satisfaction improved significantly in two areas that were previously thought to be at high risk for unfavorable comments: crew empathy and communication clarity. Crew members reported increased confidence, situational awareness, and adaptability after participating in the coaching program. The findings suggest that inflight coaching is a viable and effective strategy for improving service consistency and reducing complaint volumes in the short term. It also highlights the importance of personalized, context-driven training as a supplement to standard crew training programs. This concludes with recommendations for integrating inflight coaching into performance management frameworks and outlines future research opportunities for longitudinal impact analysis and scalability across varied airline operational contexts. These insights offer a valuable contribution to evidence-based service innovation and continuous quality improvement in commercial aviation.